The relationship of physical balance in the utilization of pelleted and nonpelleted rations for lambs-Metabolism studies. - Richardson, D.; Bell, T.D.; Cox, R.F.; Striegel, W.D. (Kansas Agricultural Experiment Station, 2011)
Studies at this station and others have shown the importance of ratio of roughage to concentrate in lamb-fattening rations. In recent years, there has been considerable interest in feeding completely pelleted rations. Tests were designed to study the effect of pelleting upon digestibility and percentage of nitrogen retained by lambs fed different ratios of roughage to concentrate, pelleted and nonpelleted. A previous test indicated lowered digestion of fiber in pelleted rations but an inerease in digestibility of other nutrients to such an extent that the total digestible nutrient values were essentially the same. Nitrogen retention was greater with the pelleted rations.
Keywords: Sheep; Pelleted ration; Nonpelleted ration; Metabolism